Pancreatitis and Pancreatopathy: Classification Characteristics, Principles of Diagnosis and Treatment in Children - Yu.V. Belousov (Zaslavsky O.Yu., 2012)
Issues of pancreatic diseases classification in children and adults are discussed. It is accentuated that none of the classifications contain «pancreatopathy» or «dyspancreatism» definitions whereas dissociative selection of basic pancreatic enzymes is a prenosological condition which usually accompany many diseases of digestive tract and it should be reflected in classification as a functional pancreatic disorder. Modern protocols of diagnosis and treatment of pancreatic diseases in children are given.